2,4,6-Trifluoroaniline - Betz, Richard (International Union of Crystallography, 2008)
The title compound, C(6)H(4)F(3)N, is a fluoro derivative of aniline. The molecule shows non-crystallographic mirror symmetry. Bond lengths are normal. The C—C—C angles show some deviation from the expected ideal values by up to 5°, a finding which is in accordance with a similar structure in the literature. In the crystal structure H⋯F contacts and H⋯N contacts lead to the formation of sheets whose surfaces are made up by the hydrophobic phenyl rings.